The identity of Senecio lancifer (Asteraceae, Senecioneae) - Wang, Long; Tong, Tian-Jing; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2016)
We clear up a taxonomic and nomenclatural confusion, in which Senecio lancifer (Asteraceae, Senecioneae) has been involved. This name is determined to belong to a Ligularia species, which is identical with L. leesicotal. The correct name of the species is L. lancifera (Drummond) Srivastava & Jeffrey.